Sistem Informasi Pemesanan Paket Pariwisata Berbasis Web Pada Smart Tour Purwokerto - Joko Dwi Mulyanto; Supriatiningsih Supriatiningsih; Iqmi Chalimah (Universitas Bina Sarana Informatika, 2018)
Abstract - In the business world, technology is very supportive to develop a business. Travel services bureaus have more and more demand. To simplify the consumer in ordering it required a computerized system. Smart Tour Purwokerto is one of the travel services bureau that has not used computerized system or still using manual system. The system used today has many weaknesses. Therefore, in this Final Project, a Web-Based Tourism Package Booking System for Purwokerto Smart Tour will be made. The research method used is the method of software development, namely the waterfall method and data collection techniques including observation, interviews and literature studies. Next step is program design. Booking information system using a programming language .The system created has 3 users, namely admin, consumer and visitor. Admin has the right to add, edit, and delete data, consumers have the right to place an order, view order history and confirm payment, visitors have the right to access the company's main page. The system that is expected to be able to improve services for consumers, especially for the Smart Tour Purwokerto. Keywords: Computerized System, Tourism Package Ordering Information System, Purwokerto Smart Tour